The Effect of Tax Literacy on Tax Compliance: The Moderating Role of Patriotism - Rosa Intansari, Maria; Supramono, Supramono (Technium Social Sciences Journal, 2022)
This study aims to examine the effect of tax literacy on tax compliance of individual taxpayers who have MSME businesses and examine the moderating role of patriotism on the effect of tax literacy on tax compliance. Collecting data using a survey through online questionnaires to individual taxpayers who have Micro, Small, and Medium Enterprises in the field of fashion, furniture, handicrafts, and other businesses besides the culinary field in Central Java. Based on the result of data collection obtained, 102 respondents and the data were analyzed using moderation Regression Anlysis. The results showed that tax literacy significantly affected MSME taxpayer compliance. Then patriotism is proven to moderate and has a significant relationship with tax litercay on tax compliance.